Analysis Of Spatial Layout And Building Form On User Comfort - Daeli, Ikhtiar Aronifati (Innovative Research in Civil and Environmental Engineering, 2025)
This study aims to analyze the influence of spatial layout and building form on user comfort in buildings. User comfort is an essential aspect of architectural design that involves physical and psychological conditions, including thermal, visual, acoustic, and spatial comfort. The research employs a quantitative approach with a descriptive-analytical method through a case study of selected buildings. Data were collected through field observations, questionnaires, interviews, and documentation to evaluate spatial organization, building form, and user comfort levels. The results indicate that well-organized spatial layouts, particularly open-plan arrangements and efficient circulation systems, significantly improve thermal, visual, and spatial comfort. Additionally, building form, including orientation, mass configuration, spatial proportion, and facade design, influences indoor environmental quality by optimizing natural lighting, ventilation, and temperature stability. The findings demonstrate that the integration of functional spatial planning and environmentally responsive building form contributes significantly to enhancing user comfort. Therefore, architectural design should consider spatial organization and building form simultaneously to create comfortable, efficient, and sustainable built environments.